1991
DOI: 10.1111/j.1744-7348.1991.tb05645.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a paclobutrazol‐based growth regulator on the yield, quality and ease of management of oilseed rape

Abstract: A mixture of paclobutrazol and chlormequat chloride plant growth regulators (JF10405, Parlay C) was tested on field crops of two 'double zero' oilseed rape cultivars in two seasons. Application rate and timing of JF10405 were varied. Very large plots enabled the use of commercial farm equipment to treat and harvest the experiments.Untreated plots showed considerable lodging at harvest in all experiments. Treatment with JF10405 had only small effects on the height of mature plants but, generally, reduced lodgin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
1
8
1
Order By: Relevance
“…At both stations it was observed that application of only triazole fungicides (Top0.5and Folicur + Proline) reduced oil content in comparison with control and other treatments [6,16]. Our results are contradicted by MertTürk et al (2008) [23] and Butkute et al (2006) [24], who worked with triazole fungicides Harvesan and Folicur, respectively, and reported that oil content of rapeseed increased significantly after triazole application in comparison with the control.…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…At both stations it was observed that application of only triazole fungicides (Top0.5and Folicur + Proline) reduced oil content in comparison with control and other treatments [6,16]. Our results are contradicted by MertTürk et al (2008) [23] and Butkute et al (2006) [24], who worked with triazole fungicides Harvesan and Folicur, respectively, and reported that oil content of rapeseed increased significantly after triazole application in comparison with the control.…”
Section: Resultscontrasting
confidence: 85%
“…Heavy-lodged plants of untreated plots attained the lowest TGW at both stations (Table 3). Due to lodging, growing conditions are unfavorable for seed filling because of reduced light, which has a negative impact on photosynthesis [16][17][18]. Severe lodging interferes with the transport of nutrients and moisture from the soil and, thus, with storage in developing seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Paclobutrazol might have a similar effect. Paclobutrazol also decreases the apical dominance of the main stem meristem and favours the formation of secondary, tertiary and quaternary branches, which also help to stabilise the crop canopy and prevent lodging through branch interlocking (Baylis & Huntley-Bull, 1991). In wheat (Fischer & Stapper, 1987), barley (Stanca, Jeukins & Hanson, 1979) and oilseed rape (Baylis & Wright, 1990), severe lodging results in smaller mean seed weights, but in lentils it did not affect mean seed weight or the mean number of seeds per pod.…”
Section: Discussionmentioning
confidence: 99%
“…Crops that were naturally or artificially lodged were more susceptible to diseases and produced lower yields than crops that were mechanically supported or prevented from lodging by treatment with plant growth retardants (Baylis & Wright, 1990). Inhibitors of gibberellin biosynthesis, such as chlormequat chloride (Saini, Jolly & Singh, 1987) and paclobutrazol (Baylis & Huntley-Bull, 1991), have been used successfully to prevent lodging and increase seed and oil yields of brassica oilseed crops. The field experiments described here were done to study effects and interactions of a foliar application of paclobutrazol and soil applications of phosphorus on the lentils.…”
Section: Introductionmentioning
confidence: 99%
“…Glucosinolates are not only considered to be involved in plant defense mechanisms (Agerbirk and Olsen 2012), but also their high content impairs the quality of oil and meal. Baylis and Hutley-Bull (1991) reported that paclobutrazole reduced glucosinolates in the seeds of rapeseed significantly in comparison with untreated seeds. In our studies, fungicide treatment coincided with the increase of indole glucosinolates and reduced content of alkenyl glucosinolates.…”
Section: Discussionmentioning
confidence: 99%